Dampak Pandemi Covid-19 : Studi Kasus Kemiskinan dan Ganggunan Kesehatan Mental di Kapanewon Seyegan, Sleman, DIY - Faidati, Nur; Sinuraya, Suci Iriani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study intends to analyze the impact of the Covid-19 pandemic on poverty and mentalhealth. Covid-19 has been going on for almost 2 years. This condition has an impact on thecommunity's economy and other social problems, just like mental health . Some peoplehave lost their livelihoods, their businesses have declined and some have even failed. Thisfurther worsens the condition of Kapanewon Seyegan which has the highest poverty ratein Sleman Regency. The research method used in this study is a qualitative researchmethod. This research was conducted in Kapanewon Seyegan, Sleman Regency, betweenJune – August 2021. Based on the research conducted, the pandemic has worsened povertyconditions in Kapanewon Seyegan. Furthermore, the pandemic also causes other problemssuch as the addition of ODGJ cases and a number of other problems. To respond to thisproblem, it is necessary to carry out community empowerment activities that can have aneconomic impact as well as community empowerment related to providing support to theODGJ community and farmer groups.